Más allá del conocimiento: los desafíos epistemológicos y sociales de la enseñanza mediante el cambio conceptual - Duschl, R. A. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
The focus of this paper is on the generic assessment practices teachers need to adopt in order tó support the shift in perspective about classroom management. This research show that actions, practices, products and discourse patterns of the classroom can provide the necessary assessment information in the episternic, cognitive, and social domains teachers need to facilitate science learning.